Pengembangan Bahan Ajar Trigonometri Dengan Pendekatan RME Berbasis Aplikasi Schoology - Sudarman, Satrio Wicaksono; Vahlia, Ira (Pendidikan Matematika Universitas PGRI Yogyakarta, 2018)
This study aims to determine the benefits of teaching materials based on the application of Schoology in the course of trigonometry in the lecture. One of the hallmarks of Schoology-based teaching materials is to use the Schoology app which is one of the web-based social web pages which offers the same learning as in a class free and easy to use. Through Schoology, the management of learning is very easy. Schoology is also almost the same function with other web pages in which it offers lecturers to load materials, learning materials, structured quizzes. This research is a kind of research development. Research methodology used as follows: (1) research and information gathering, (2) planning, (3) product development, (4) initial test, (5) product revision, (6) field trial, (7) field trial products, (8) product operational trials, (9) product revisions and (10) implementation. The achievement of this research is teaching materials based on Schoology which can support lecturer of trigonometry in the mathematics education program. This teaching material is feasible to use and the achievements generated in the development of teaching materials based on this schoology is to improve students' learning outcomes in trigonometric courses.Keywords: development, Â teaching materials, schoology, trigonometry